Exploring the Intersection of Religion and Cinema: Trends and Reflections in Contemporary Film Culture - Linze, Li; Desa, M. Asyiek Mat (Journal of Ecohumanism, 2024)
This article delves into the complex relationship between religion and film, and studies the latest trends and ethical reflections in the field of film culture. Through an interdisciplinary perspective, this article explores how movies serve as a medium for communication between audiences and religion. By paying attention to the use of religious symbols and themes in movies, audiences are invited to reflect on spiritual themes and religious culture. The analysis of the social response of religious expressions in movies highlights the interactive relationship between social beliefs, cultural backgrounds, and religious narratives. This study focuses on the rich and diverse interpretations of religious themes in global film works by showcasing different depictions of religious elements in global films. In addition, the study also explored the role of film festivals as active platforms for religious dialogue and cross-cultural exchange, promoting a deeper understanding of religious diversity in contemporary society. The article also showcases the constantly evolving trend of religion in movies, as well as the ongoing academic enthusiasm for the ethical significance of depicting religious elements in movies.